2017
DOI: 10.33546/bnj.161
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Combination of Kangaroo Mother Care Method and Lullaby Music Therapy on Vital Sign Change in Infants With Low Birth Weight

Abstract: Background: Kangaroo mother care (KMC) and lullaby music methods have been considered as the alternative treatment for vital sign changes in low birth weight infants. However, little is known about the combination of the two methods.Objective: To identify effectiveness of combinations of Kangaroo mother care and Lullaby music methods on changes in vital signs in low birth weight infants.Methods: A quasi experiment with non-equivalent control group design. This study was conducted on October– December 2016 at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Oxygen saturation slightly increased during combination therapy. Ettenberger and colleagues, as well as Yusuf and colleagues also found an increase in oxygen saturation during combination therapy [ 28 , 29 ]. The decrease after LPMT that we found is in contrast with several recent meta-analyses investigating the physiological effects of music therapy alone, which reported improvement or stabilization of oxygen saturation [ 18 , 20 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen saturation slightly increased during combination therapy. Ettenberger and colleagues, as well as Yusuf and colleagues also found an increase in oxygen saturation during combination therapy [ 28 , 29 ]. The decrease after LPMT that we found is in contrast with several recent meta-analyses investigating the physiological effects of music therapy alone, which reported improvement or stabilization of oxygen saturation [ 18 , 20 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These effects were only short-term, as after combined interventions physiological parameters returned to initial values. Regardless of the variation in the methodological approach, other studies investigating the effects of combination therapy generally also reported stable or slightly beneficial changes in vital parameters during and after combination therapy [ 24 , 28 , 29 , 30 , 31 , 40 ]. Previous studies have reported that both KC and music therapy are well accepted, cost-effective, accessible, and safe methods that improve physiological parameters and neurodevelopmental outcomes, and reduce infant stress [ 13 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Similar results were also explained in another study which explained that the kangaroo method affected body temperature in infants with low birth weight as evidenced by an increase in body temperature for infants. 10,11 Birth weight is an important indicator of the health of the baby, a major factor for survival and a factor for the development and mental development of the baby in the Fenny Dwi Kurniasih / Kangaroo Method Treatment Increases Baby's Body Temperature With Low Birth Weight future. In terms of maternal factors, several factors affect LBW, including pregnancy and fetal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Chou et al (2015) found that music therapy intervention in the infant environment during development leads to better oxygenation of the infant and possibly increases brain development [3]. Yusuf Nova et al (2017) also highlighted the effectiveness of a combination of kangaroo care and music interventions in the neonatal intensive care unit and even after discharge [11]. Rahimi et al (2017) reported that educating nurses and physicians about non-pharmacological control of pain in infants by sucrose and swaddling and limiting painful processes can prevent stress to the infant [6].…”
Section: Introductionmentioning
confidence: 99%